2013
DOI: 10.1117/1.jbo.18.10.105003
|View full text |Cite
|
Sign up to set email alerts
|

Depth-dependent refractive index of normal and early degenerated articular cartilage

Abstract: Abstract. The depth distributions of refractive index (RI) in normal and early degenerated articular cartilage (AC) were measured and correlated to the pathological statuses. Utilizing a confocal microscope, the depth distribution of RI was determined with an interval of 50 μm from the articular surface and approximated as a smooth curve. The fluctuation of RI was quantified with a specially defined coefficient and the proteoglycan (PG) loss was quantified with histological images. The overall RI of the AC col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…However, most of authors report only the average value of cartilage refractive index. The available data have high variation: 1.3975±0.0156 (λ=561nm) , 1.4444±0.0363 (λ=561nm) , 1.358±0.022 (λ=1310nm) , 1.510±0.009 (λ=1300nm) , explained among others by different light source, age, water content and physiological status of the sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of authors report only the average value of cartilage refractive index. The available data have high variation: 1.3975±0.0156 (λ=561nm) , 1.4444±0.0363 (λ=561nm) , 1.358±0.022 (λ=1310nm) , 1.510±0.009 (λ=1300nm) , explained among others by different light source, age, water content and physiological status of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that before the optical clearing the refractive index value of cartilage averaged over four samples was 1.386±0.008 which is close to the values obtained in Refs. . Refractive index value measured for the same tissue samples after 100 min of optical clearing with iohexol solution was 1.504±0.016.…”
Section: Resultsmentioning
confidence: 99%
“…Thickness is converted from optical path length by assuming an average refractive index n ¼ 1.444 in articular cartilage. 23 For sample S1, region R-1 is relatively thin with a thickness of ∼125 μm. Region R-2 is twice thicker than R-1, which is consistent with the anatomical knowledge about the thickness of superficial and transitional zones.…”
Section: Data Processing Of Slope-based Segmentationmentioning
confidence: 99%
“…Our previous study has reported that the depth-dependent property of RI was related to PGs in AC tissue. 18 The impact of mechanical wear and biochemical alteration to the depth distribution of RI still need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The depth fluctuation of RI was characterized by using a previously developed method. 18 2 Materials and Methods…”
Section: Introductionmentioning
confidence: 99%